Relationship between remnant hippocampus and amygdala and memory outcomes after stereotactic surgery for mesial temporal lobe epilepsy - Malikova, Hana (Neuropsychiatr Dis Treat, 2015)
BACKGROUND AND PURPOSE: Mesial temporal structures play an important role in human memory. In mesial temporal lobe epilepsy (MTLE), seizure activity is generated from the same structures. Surgery is the definitive treatment for medically intractable MTLE. In addition to standard temporal lobe microsurgical resection, stereotactic radiofrequency amygdalohippocampectomy (SAHE) is used as an alternative MTLE treatment. While memory impairments after standard epilepsy surgery are well known, it has been shown that memory decline is not a feature of SAHE. The aim of the present study was to correlate the volume of the remnant hippocampus and amygdala in patients treated by SAHE with changes in memory parameters. MATERIALS AND METHODS: Thirty-seven MTLE patients treated by SAHE (ten right, 27 left) were included. Patients underwent magnetic resonance imaging examinations including hippocampal and amygdalar volumetry and neuropsychological evaluation preoperatively and 1 year after surgery. RESULTS: Using Spearman correlation analyses, larger left-sided hippocampal reductions were associated with lower verbal memory performance (ρ=−0.46; P=0.02). On the contrary, improvement of global memory quotient (MQ) was positively correlated with larger right-sided hippocampal reduction (ρ=0.66; P=0.04). Similarly, positive correlations between the extent of right amygdalar reduction and verbal MQ (ρ=0.74; P=0.02) and global MQ change (ρ=0.69; P=0.03) were found. Thus, larger right hippocampal and amygdalar reduction was associated with higher global and verbal MQ change after SAHE. CONCLUSION: Larger left-sided hippocampal reductions were associated with lower verbal memory performance. This finding is in accordance with the material-specific model of human memory, which states that the dominant hemisphere is specialized for the learning and recall of verbal information. We hypothesize that larger right-sided ablations enable the left temporal lobe to support memory more effectively, perhaps as a consequence of epileptiform discharges spreading from remnants of right mesiotemporal structures to the left.